Story recognition, “plot-gene” access and retrieval from the “mental sketchpad”: case-study (Yvan Attal’s film “Ils sont partout” and its ancient counterparts) - Levitski, Olga (2019)
The article presents a case study which exemplifies the cognitive process of “plot-gene”1 recognition and its retrieval from the memory-’s “mental sketchpad”.2 Specifically, the article analyzes four cinematic representations, in which the same “plot-gene” – a pejorative take on the birth of Jesus – is found: the movie by Yvan Attal titled “Ils sont partout” (available on Neflix as “They are everywhere”), the movie “Life of Brian” by “Monty Python”, the movie “Jesus of Montreal” by Denys Arcand, as well as several anti-religious sketches by the British comedian Rowan Atkinson. These movies are considered in the article at the level of their cinematic plots and narrative schema, as well as at the ideological level. The article provides comparative data for the identification of the same plot-gene in different contexts that date back to antiquity and can be found cross-culturally worldwide. The article utilizes the motif-compass method developed by the Russian scholar Olga Freidenberg. In conclusion, the article postulates the hypothesis that the plot-gene under investigation always resurges due to the specific ideological reasons (i.e., resistance strategy towards AntiSemitism, expression of anti-clerical sentiments).
Keywords: narrative schemata; storage and retrieval; narratology and comparative method; memory; cognition; plot-gene and mental sketchpad; Olga Freidenberg’s “motif compass” method, Yvan Attal’s movie “Ils sont partout” (“They are everywhere”)